ANALISIS PENERAPAN ICE BREAKING DALAM KURIKULUM MERDEKA DI SD NEGERI 002 BENAI KABUPATEN KUANTAN SINGINGI - Maisurah, Dita; Antosa, Zariul; Guslinda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of ice breaking in the Merdeka Curriculum and its effect on improving the learning concentration of fourth-grade students at SD Negeri 002 Benai, Kuantan Singingi Regency. The background of this study is based on the low level of students’ learning concentration, which is indicated by a lack of focus, difficulty in following instructions, and low responsiveness during the learning process. This research employed a quantitative approach with a pre-experimental method using a one group pretest-posttest design. The research subjects consisted of 25 fourth-grade students. Data collection techniques included observation, questionnaires, and interviews, with indicators of learning concentration covering focus of attention, ability to follow instructions, and response to learning activities.The results of the study indicate that the implementation of ice breaking significantly improves students’ learning concentration. After the treatment, students showed improvement in paying attention to the teacher’s explanations, were better able to follow instructions, and demonstrated more active responses during learning activities. Ice breaking activities implemented in the form of simple games, motivational claps, and interactive activities proved effective in creating a fun and conducive learning environment. In addition, the analysis results showed a significant difference between pretest and posttest scores, indicating a positive effect of ice breaking implementation.In conclusion, ice breaking is an effective learning strategy for improving students’ learning concentration in the Merdeka Curriculum. Proper implementation can help reduce boredom, increase student engagement, and create a more active and enjoyable learning environment. Therefore, teachers are encouraged to optimally integrate ice breaking into the learning process